1992
DOI: 10.1177/0022427892029003002
|View full text |Cite
|
Sign up to set email alerts
|

Gang Involvement and Delinquency among Hispanic and African-American Adolescent Males

Abstract: The application of Rasch modeling to survey responses and official records of 139 Hispanic and 300 African-American males in the sixth through eighth grades at four Chicago inner-city schools is used to construct incremental measures of gang involvement and delinquency. Scale sequence and regression analysis suggest that different social processes operate in gang involvement for the two ethnic populations. In both sets of cross-sectional data, the fitting of linear structural models shows gang involvement to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(94 citation statements)
references
References 11 publications
4
88
1
1
Order By: Relevance
“…Research with female adolescents suggests that peer influences, dysfunctional families and living in neighborhoods characterized by low educational opportunities, violence, and poverty play a role in female gang involvement (Molidor, 1996;Walker & Mason, 2001). Other research has shown that among African American populations, environmental factors such as the presence of drug dealers in the neighborhood, having peers who use drugs, and having a family member who belongs to a gang were predictors of gang membership (Curry & Spergel, 1992). It may be that among our sample of detained youth, especially the females and the Black adolescents, they are trying to feel a sense of belonging and power by joining a gang because they are afraid, or they may be seeking protection from the violence they witness in their community.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Research with female adolescents suggests that peer influences, dysfunctional families and living in neighborhoods characterized by low educational opportunities, violence, and poverty play a role in female gang involvement (Molidor, 1996;Walker & Mason, 2001). Other research has shown that among African American populations, environmental factors such as the presence of drug dealers in the neighborhood, having peers who use drugs, and having a family member who belongs to a gang were predictors of gang membership (Curry & Spergel, 1992). It may be that among our sample of detained youth, especially the females and the Black adolescents, they are trying to feel a sense of belonging and power by joining a gang because they are afraid, or they may be seeking protection from the violence they witness in their community.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, in communities plagued by high levels of violence, respect may equate with safety as they are proffered some level of protection through their gang membership. There has been some research highlighting the interrelationship of gang involvement, delinquency and social contexts (e.g., Curry & Spergel, 1992); however, future research should investigate these specific underlying motivating factors among this population to understand their reasons for gang involvement so that intervention efforts can be developed. Moreover, these studies should examine the differential gender and racial/ethnic factors involved so that efforts can be tailored.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, students are in a stage of identity development in which they begin to think about their place in the world and question the reality of their educational opportunities and the barriers they face. Gang research suggests that for Hispanic students, lack of school opportunities and educational frustration were critical in the development of a gang identity (Curry & Spergel, 1992;Freng & Esbensen, 2007).…”
Section: The Transition To High Schoolmentioning
confidence: 99%
“…Researchers, theorists, and practitioners in the fields of criminology and forensic science often use the terms "youth gang", "youth offending" and "juvenile delinquency" interchangeably. Although "youth offending" and "juvenile delinquency" cannot be equated with "youth gang activity" as such, youth gang membership does play a major role in offending behaviour (White and Mason 2006;White 2002), and it appears that youth offending is closely connected to antisocial behaviour by unorganised youths operating in relatively small peer groups (Curry and Spergel 1992). Nevertheless, the behavioural attributes of youth gangs and young offenders suggest that they are both implicated in antisocial behaviour, but the level of involvement and modes differ.…”
Section: Risk Factors To Youth Gangs' Membership and Substance Misusementioning
confidence: 99%
“…This is because growing up in disadvantaged neighbourhoods characterised by poor living conditions, low neighbourhood attachment, high unemployment, and a general feeling of hopelessness appear to be amongst the more important community risk factor associated with youth gang involvement and substance misuse behaviour (Pakes and Winstone 2007;Taylor 2002;Thornberry et al 2003). Research demonstrates that there is a significant link between disorganised community and the availability of illicit drugs and alcohol with an increased risk that young people will use drugs and alcohol illegally (Bjerregaard and Smith 1993;Curry and Spergel 1992;Pakes and Winstone 2007;Thornberry et al 2003). Several studies have also examined the relationship between family structure and antisocial behaviour, and suggest inadequate parenting practices due to large family size as a major risk factor for youth gang membership and antisocial behaviour (for a review, see Andrews and Bonta 2006;Bjerregaard and Smith 1993;Henry et al 2001).…”
Section: Risk Factors To Youth Gangs' Membership and Substance Misusementioning
confidence: 99%